At the limits of the rule of law: EU-US counter-terrorism cooperation - Annegret Bendiek (Stiftung Wissenschaft und Politik (SWP), 2011)
Ever since 9/11, the United States has considered terrorism as an existential threat to its security and one of the country's reactions to this threat was launching a military intervention in Afghanistan. The EU and its member states, on the other hand, view terrorism as a problem of internal security. Enforcing transatlantic counter-terrorism policy poses a dilemma: deciding in each case between a strict orientation towards the principles of the rule of law or a greater emphasis on concrete protection measures and the concomitant security policy needs. From the European perspective, making this decision might in some cases mean having to choose between transatlantic cooperation and acting independently - in other words, deciding for or against cooperation with the United States. Against this backdrop, the following questions arise: Has the policy of the Obama administration or the EU's enhanced capacity to act following the entry into force of the Lisbon Treaty given fresh impetus to the transatlantic community of values? Or do the differences stemming from the years of the Bush administration still remain? To paraphrase a frequently quoted thesis by Robert Kagan, how far are "Mars" and "Venus" really from one another in the field of counter-terrorism? And finally: What are the implications of the transatlantic rift for future cooperation between the EU and the United States? The broad differences of opinion on important issues such as data protection, terrorist lists, military prisons and extraordinary renditions can be explained by the divergent perceptions in the EU and the United States of the relationship between security and the rule of law. The findings of this study present a differentiated picture of the situation
Keywords: 320